2010
DOI: 10.1111/j.1937-2817.2010.tb01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance and Species Richness of Birds in Common Reed Habitats in Lake Erie

Abstract: Common reed (Phragmites australis) forms dense stands with deep layers of residual organic matter that negatively affects plant diversity and possibly habitat use by wetland birds. We sought to determine whether seasonal relative abundance and species richness of birds varied among 3 habitat types in Great Lakes coastal wetland complexes recently invaded by common reed. We used fixed‐distance point counts to determine species relative abundances and species richness in edge and interior locales within common r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Studies of the impacts of common reed on other taxa have shown decreased fish abundance (Able et al, 2003), but minimal impacts on macroinvertebrate diversity (Holomuzki & Klarer, 2010). In some cases, common reed may benefit native species, such as land birds (Meyer et al, 2010).…”
Section: Genes Invasions and Competitionmentioning
confidence: 99%
“…Studies of the impacts of common reed on other taxa have shown decreased fish abundance (Able et al, 2003), but minimal impacts on macroinvertebrate diversity (Holomuzki & Klarer, 2010). In some cases, common reed may benefit native species, such as land birds (Meyer et al, 2010).…”
Section: Genes Invasions and Competitionmentioning
confidence: 99%
“…For many mosquito species, dense plant growth is a preferred adult resting site (Schreiber et al 1989 , Irby andApperson 1992 ), and host-seeking females typically forage within or along the interface of these habitats (Bidlingmayer 1971 , Lothrop andReisen 2001 ). Cattail and phragmites stands also provide nesting and food resources for many urban-tolerant bird species (Bernstein and McLean 1980, Holt and Buchsbaum 2000, Sparling et al 2007, Meyer et al 2010, Kiviat 2013, including important WNVamplifying hosts such as the House Sparrow ( Passer domesticus ) and the American Robin ( Turdus migratorius ) (Kilpatrick et al 2006, Hamer et al 2009 ). Following the breeding season, phragmites and cattail stands may host dense aggregations of American Robins, European Starlings ( Sturnus vulgaris ), Common Grackles ( Quiscalus quiscula ), Red-winged Blackbirds ( Agelaius phoeniceus ), or other communal roosting species (Johnson and Caslick 1982, Caccamise and Fischl 1985, Linz et al 1991, Diuk-Wasser et al 2010, Kiviat 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal changes and functional and structural responses by bird communities is an important research focus for community ecology, and many studies have been conducted in natural habitats and agroecosystems (Loiselle and Blake 1992, Kwok 1996, Kwok and Corlett 1999, Isacch et al 2003, Meyer et al 2010. Few studies have discussed the effects of season on birds in urban areas, and some conducted in Europe and North America have found that season affects species richness of urban bird communities and the nestedness pattern that occurs when species assemblages in relatively species-poor patches comprise successive subsets of the species present at richer sites (Patterson 1987, Suhonen and Jokimäki 1988, Wright and Reeves 1992, Jokimäki et al 1996, Caula et al 2008, Murgui 2010.…”
mentioning
confidence: 99%